Philosophical Category of Integration as a Condition of Economic Systems Development - Puzanova, Irina (Տիգրան Մեծ)
The article analyzes the concept of integration in dialectic unity with differentiation by its application during the study of economic systems development, including supply chains. The differentiation is a problem, i.e. the nature of occurrence of a critical situation in the system stipulating the need to generate new goals for the interaction of its components; integration is a solution to a problem, the basis for the transition to a new stage of system development. The study results reveal that the main integration drivers are factors that ensure the complementarity and compatibility of system components. It is stated that the functionality is the first condition for integration, that is, the potential for the unhindered implementation of individual goals and objectives which are not destructive to the system. The homology is the second condition, which ensures the compatibility of system components. The integratedness is the third condition that can be defined as the degree of firmness of links between system parts on which the system stability and viability depend. The author notes the importance of permanent diagnostics of connections within and between the economic system and environment since inter-organizational links constitute a differentiation factor.
Keywords: Philosophy of economics